The dynamic linkage between climate change and agricultural food production in Ethiopia with the application of a novel dynamic ARDL simulation method - Dejene Fikadie Wudie (Environmental Research Communications)
This study investigates the dynamic relationship between climate change and agricultural food production in Ethiopia by employing a novel dynamic autoregressive distributed lag (ARDL) simulation approach. Annual time-series data from 1993 to 2023 were used in the analysis. The important climate variables, such as temperature, precipitation, humidity, and carbon dioxide emissions that influence agricultural output while also incorporating policy related variables including fertilizer use, pesticide application, and cultivated land. The results revealed that temperature, humidity, and carbon dioxide (CO _2 ) emissions exert a significant positive influence on food production in both the short and long run. In contrast, precipitation and cultivated land area exhibited negative effects on agricultural output. Moreover, policy variables such as fertilizer and pesticide usage are found to positively and significantly enhance food production over time. The findings emphasize the importance of agricultural inputs and land use policies in enhancing resilience to climate-induced shocks. On the basis of these findings, policymakers aiming to develop climate-resilient agricultural strategies emphasize the importance of integrating climate adaptation into national agricultural planning. Furthermore, policymakers prioritize sustainable land management and invest in technologies and practices that strengthen long-term food security under changing climatic conditions.